A study on different plant species of the Rosaceae family and their ethnobotanical uses among the local communities at Swat district, Pakistan - Ali, Shujat (Ethnobotany Research and Applications, 2023)
Background: The study area possess 55 plants of the family Rosaceae, which are widely used traditionally throughout the area. The family contains a range of plants that have high ethnobotanical and economical value. The family is well-known for its economically valuable fruits and medicinal plants. As a result, the purpose of this study was to collect ethnobotanical data of the Rosaceae family from Swat district in order to provide comprehensive documentation for future research. Methods: The ethnobotanical data was collected from 2021 to 2022 from 80 respondents by using semi-structured questionnaires, open-ended questionnaires, and personal observations. The interviewed participants were mostly herbalists, farmers, folk healers, shepherds, and knowledgeable group members, age from 30 to 80 years. All the collected data was analyzed through Microsoft Excel (2016). Results: There were 55 plant species of the family Rosaceae existing in the area, including 7 (13%) climbing shrubs, 19 (34%) herbs, 11 (20%) shrubs, and 18 (33%) tree species. Results of the present study showed that 85% of the plants in the family were utilized as medicinal in the area, followed by honeybees (44%), fuel wood (33%), foods (33%), fodder (31%), fencing (25%), ornamentals (14%), timber (7%), and (7%) plants were used for making agricultural tools. The most common part used as medicine was fruits (43%), followed by shoot (30%), leaves (13%), flowers (6%), roots (4%) and other parts were used (4%). Powder was the most commonly used preparation method (32%), followed by decoction (28%), direct consumption (19%), juice extraction (17%), and other methods (6%). Results of the present study indicated that plants of the family Rosaceae were highly economical for the native communities of the area. Conclusion: This study provides awareness to the native community and the worldwide trend towards native information, regeneration and transmission of knowledge. Furthermore, this study of the family's ethnobotanical uses will provide a foundation for future research in the family. Keywords: Ethnobotanical, Diversity, Family Rosaceae, Swat